Parametric Urban Models Based on Frei Otto's Generative Form-Finding Processes - Lopes, J. V.; Paio, A.; Sousa, J. (Proceedings of the 19th International Conference on ComputerAided Architectural Design Research in Asia CAADRIA, 2014)
Presently there is a progressive tendency to incorporate parametric design strategies in urban planning and design. Although the computational technologies that allow it are recent, fundamental theories and thinking processes behind it can be traced back to the work conducted at the Institute for Lightweight Structures (IL) in Stuttgart, between the 1960’s and 1980’s. This paper describes an ex- perimental urban research work based on Frei Otto and Eda Schaur's thoughts on unplanned settlements, and on the form-finding experi- ences carried out at IL. By exploring the digital development of para- metric and algorithmic interactive models, two urban design proposals were developed for a site in Porto city. Out of this experience, this pa- per suggests that today the act of design can benefit from a deeper un- derstanding of the natural processes of occupation and connection.